2015
DOI: 10.1073/pnas.1421968112
|View full text |Cite
|
Sign up to set email alerts
|

Species fluctuations sustained by a cyclic succession at the edge of chaos

Abstract: Although mathematical models and laboratory experiments have shown that species interactions can generate chaos, field evidence of chaos in natural ecosystems is rare. We report on a pristine rocky intertidal community located in one of the world's oldest marine reserves that has displayed a complex cyclic succession for more than 20 y. Bare rock was colonized by barnacles and crustose algae, they were overgrown by mussels, and the subsequent detachment of the mussels returned bare rock again. These processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
176
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(184 citation statements)
references
References 46 publications
(63 reference statements)
5
176
0
3
Order By: Relevance
“…The cyclic fluctuations of the populations in this community become irregular through the seasonality of the system and the time needed for the establishment of each of the species. Interestingly, the cyclic replacement is reminiscent of rock-paper-scissor interactions (Benincà et al 2015) but the dynamics do not resemble those of the E. coli strains described above (Kerr et al 2002). The reason might be that with sessile stages but global dispersal of recruits the intertidal community is neither global (leading to the dominance of a single species in the well-mixed flasks), nor completely spatially structured (resulting in balanced chasing at patch edges and overall stability).…”
Section: Coexistence Mechanisms May Results In Unpredictable Dynamicsmentioning
confidence: 98%
See 1 more Smart Citation
“…The cyclic fluctuations of the populations in this community become irregular through the seasonality of the system and the time needed for the establishment of each of the species. Interestingly, the cyclic replacement is reminiscent of rock-paper-scissor interactions (Benincà et al 2015) but the dynamics do not resemble those of the E. coli strains described above (Kerr et al 2002). The reason might be that with sessile stages but global dispersal of recruits the intertidal community is neither global (leading to the dominance of a single species in the well-mixed flasks), nor completely spatially structured (resulting in balanced chasing at patch edges and overall stability).…”
Section: Coexistence Mechanisms May Results In Unpredictable Dynamicsmentioning
confidence: 98%
“…from competition and predation process (Huisman and Weissing 1999). Recently, Benincà et al (2015) demonstrated for the first time that near-chaotic dynamics may occur in the world outside. In an intertidal ecosystem in New Zealand, cyclic replacements occur of barnacles colonizing bare rock, brown alga overgrowing barnacles, mussels settling on barnacles and algae, giving rise to bare rock as the mussels eventually detach.…”
Section: Coexistence Mechanisms May Results In Unpredictable Dynamicsmentioning
confidence: 99%
“…[11]), and factors affecting this variability, generally classified into environmental effects or endogenous density-dependent processes, are numerous (e.g. [1219]) and interact in complex ways [2021]. …”
Section: Introductionmentioning
confidence: 99%
“…Анализ таких систем представляет особый интерес, поскольку факторы генерации хаоса заложены в саму основу жизненного цикла клетки. Однако, в отличие от других уровней организации живой природы, для которых существуют убедительные примеры явления хаоса (так функционируют природные экосистемы [12], такой может быть стратегия поиска пищи у моллюска [13], так формируется пигментация у некоторых видов моллюсков [14][15][16], возникают спорадические эпидемии [17] и происходят вспышки численности в популяциях хищников, грызунов, и насекомых [18][19][20][21], так проявляются различные заболевания [22][23][24][25][26][27] и др. ), на внутриклеточном уровне, in vivo, экспериментально доказанных примеров хаоса нет, хотя теоретически он предсказан в различных молекулярно-генетических и метаболических системах [1, 10,11,[28][29][30][31][32][33][34].…”
Section: Introductionunclassified